2015
DOI: 10.3174/ajnr.a4379
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Edema in Posterior Reversible Encephalopathy Syndrome: Correlation of MRI Features with Serum Albumin Levels

Abstract: BACKGROUND AND PURPOSE:Posterior reversible encephalopathy syndrome is a clinicoradiologic entity with typical MR imaging showing predominant vasogenic and occasional cytotoxic edema. It is unclear whether MR imaging correlates with levels of serum albumin. We determined potential risk factors for development of cytotoxic edema in posterior reversible encephalopathy syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 34 publications
0
33
0
1
Order By: Relevance
“…Cytotoxic edema has been described in a relatively lower percentage of patients with posterior reversible encephalopathy syndrome. 25 Central-variant posterior reversible encephalopathy syndrome had been described as brain stem or basal ganglia involvement that spares the cerebral cortex and subcortical white matter. 26 Imaging findings of central variant posterior reversible encephalopathy syndrome include symmetric or asymmetric vasogenic edema (the pons and basal ganglia [caudate nucleus, globus pallidus, and not resulting in the LFS]; and, rarely, the thalamus, posterior limb of the internal capsule, cerebellum, periventricular white matter) without any foci of reduced diffusivity and multiple microhemorrhages in the affected regions on susceptibility-weighted images.…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxic edema has been described in a relatively lower percentage of patients with posterior reversible encephalopathy syndrome. 25 Central-variant posterior reversible encephalopathy syndrome had been described as brain stem or basal ganglia involvement that spares the cerebral cortex and subcortical white matter. 26 Imaging findings of central variant posterior reversible encephalopathy syndrome include symmetric or asymmetric vasogenic edema (the pons and basal ganglia [caudate nucleus, globus pallidus, and not resulting in the LFS]; and, rarely, the thalamus, posterior limb of the internal capsule, cerebellum, periventricular white matter) without any foci of reduced diffusivity and multiple microhemorrhages in the affected regions on susceptibility-weighted images.…”
Section: Discussionmentioning
confidence: 99%
“…Pirker et al reported that vasogenic oedema in PRES was much more frequent in patients with decreased levels of serum albumin, whereas cytotoxic components occurred more frequently in patients with normal levels. Gao et al found that cytotoxic oedema or ischaemia was often seen in larger areas or to a higher extent of vasogenic oedema, which is probably related to local decreased perfusion and arteriolopathy 56. Both Gao and Pirker observed decreased serum albumin in up to 85% of PRES patients with miscellaneous aetiology.…”
Section: Prognosismentioning
confidence: 98%
“…In a recent retrospective chart review, the authors found that pre-existing diabetes mellitus and corpus callosum involvement of PRES-associated lesions were strong predictors of poor outcome 55. Although the presence and degree of elevated blood pressure have been shown in many studies, these do not correlate with either the clinical outcome or MRI severity or grading of vasogenic oedema 3 7 10 56. Accordingly, Singer and colleagues have observed a complete resolution of neurological signs and symptoms in 84% of cancer patients with PRES, with the neuroimaging being reversible in 81%; notably, the mortality rate in that cohort was reported to be 19% but, none of the deaths were directly associated with PRES 57 58.…”
Section: Prognosismentioning
confidence: 99%
“…Hypomagnesemia during the first 48 h after onset was reported in a cohort of patients with PRES of varying etiology [36]. Both Gao and Pirker et al observed decreased serum albumin in up to 85% of patients with PRES of miscellaneous etiology [37, 38]. …”
Section: Diagnosismentioning
confidence: 99%